Clinical Supervision with Nurses' Work Motivation in Hospital: A Survey Study - Pulungan, Tasya Ramadani; Arruum , Diah (Caring: Indonesian Journal of Nursing Science, 2025)
Nursing care is a key component of quality healthcare services, ensuring patient satisfaction and meeting hospital needs. However, patient dissatisfaction could reduce the quality of nursing care, caused by low nurses' work motivation. Clinical supervision was a form of coaching that increased nurses' work motivation through formative, restorative, and normative functions. Therefore, this study aimed to identify clinical supervision and work motivation of nurses providing care in Regional General Hospital. A descriptive correlation design was adopted with a cross-sectional method. Data were collected through a survey of 98 impatient nurses selected using simple random sampling. The survey used questionnaires that measured clinical supervision and work motivation, and then bivariate test analysis was carried out with the Spearman rho test. The results showed a significant relationship between clinical supervision and nurses' work motivation (p < 0.05), with a strong relationship strength (r = 0.637). Furthermore, the highest clinical supervision and work motivation were formative and intrinsic, respectively. In conclusion, effective clinical supervision can increase nurses' work motivation during work and contribute to the quality of nursing care in the hospital. This study recommended the continuous implementation of clinical supervision by room managers on an ongoing basis. Strategies for developing clinical supervision for nurses are important to increase nurses' work motivation to have an effective impact on performance in hospital.